1989
DOI: 10.1210/endo-125-3-1303
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Restoration of Advanced Spermatogenic Cells in Adult Male Rats Made Azoospermic by Active Immunization against Luteinizing Hormone or Gonadotropin-Releasing Hormone*

Abstract: The ability of testosterone to quantitatively restore spermatogenesis in rats made azoospermic by active immunization against LH or GnRH was examined. Sexually mature adult male rats (n = 15/group) were actively immunized against ovine LH or GnRH-human serum globulin conjugate, while control rats (n = 10) were injected with saline. After 10 weeks of immunization, five rats per group were euthanized. For each rat, trunk blood was collected for determination of LH, FSH, and testosterone by RIA; seminiferous tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 0 publications
2
30
1
1
Order By: Relevance
“…Singh et al (1995) showed that androgen alone in the complete absence of FSH could initiate spermatogenesis in the hypogonadal (hpg) mouse. Some other studies have also demonstrated the same phenomenon in the rat (Ahmad et al 1973, Awoniyi et al 1989. In contrast, there are also studies emphasizing that both testosterone and FSH are needed for maintenance of spermatogenesis in the rat (Santulli et al 1990, McLachlan et al 1994).…”
Section: Discussionmentioning
confidence: 82%
“…Singh et al (1995) showed that androgen alone in the complete absence of FSH could initiate spermatogenesis in the hypogonadal (hpg) mouse. Some other studies have also demonstrated the same phenomenon in the rat (Ahmad et al 1973, Awoniyi et al 1989. In contrast, there are also studies emphasizing that both testosterone and FSH are needed for maintenance of spermatogenesis in the rat (Santulli et al 1990, McLachlan et al 1994).…”
Section: Discussionmentioning
confidence: 82%
“…The hypothesis that combined administration of both FSH and testosterone may be required for the quantitative restoration of spermatogenesis has been widely accepted by many researchers [ I , 10-121. On the other hand, Awoniyi et al [2] reported that exogenously administrated testosterone alone is capable of quantitatively restoring spermatogenesis. We agree with the results of their report; however, spermatogenesis was completely restored by the administration of both FSH and testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ser possível ocorrer espermatogênese sem a presença de FSH (AWONIYI et al, 1989b;McLACHLAN et al, 1996;ZIRKIN et al, 1986), diversos estudos in vivo utilizando ratos como modelo animal demonstram a necessidade de LH e FSH no processo de divisão ao qual as espermatogônias e os espermatócitos estão submetidos durante a espermatogênese.…”
Section: Eixo Hipotálamo-hipófise-gônadasunclassified